(untitled) (Universal International Scientific Journal, 2026)
This article examines the formal, structural, and morphological features of diplomatic terminology in the Russian and Uzbek languages. The study is based on a linguistic approach to terminology analysis and aims to identify the main types of word terms and phrase terms, their word-formation patterns, and structural characteristics. Particular attention is paid to the classification of single-word terms into root, affix, and compound terms, as well as to the analysis of symbolic terms and abbreviated formations. Typical morphological and syntactic models of terminological combinations are examined, including constructions with nouns, adjectives, and numerals. As a result, common trends in the structural organization of diplomatic vocabulary in these two languages ​​with different systems are identified and both isomorphic and allomorphic features of their formal representation are established.